2018
DOI: 10.1093/geront/gny107
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancies With Depression by Age of Migration and Gender Among Older Mexican Americans

Abstract: Our results highlight the heterogeneity among older Mexican Americans in life expectancies with depression. These findings illustrate the importance of considering age of migration as a high-risk factor for depression among Mexican-origin immigrants. Including this risk factor as a part of depression screening is a key step for timely interventions in preventing disability and comorbidities associated with untreated depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
“…Prior work has shown that poverty and financial strain, as SDH, may contribute to increased risk of depression in racial/ethnic minority older adults compared to non-Latinx Whites (Angel et al, 2003; García et al, 2019; Kahn & Fazio, 2005). Economic difficulties can expose these minorities to additional stressors (e.g., lack of food, medicine, and utilities), further increasing their vulnerability to depressive symptoms (Chiriboga et al, 2002; Krause, 1987; Krause et al, 1991).…”
Section: Social Determinants Of Health Frameworkmentioning
confidence: 99%
“…Further, the focus is not on Mexican culture, per se, but on a cultural model that takes shape as women from all over Mexico converge in a relatively new immigrant destination in the U.S., where both daily activities and long-term goals are renegotiated and adapted to the new setting and where the ability to act on these goals is subject to a common set of social and structural constraints, regardless of documentation status. We limited the focus to women because Mexican women are twice as likely to develop symptoms of depression as Mexican men [2][3][4][5][6] and because gender shapes the migration and acculturation experience in important ways [2,48].…”
Section: Participants and Sampling Proceduresmentioning
confidence: 99%
“…As Mexican immigrants make up the single largest cohort of Hispanic/Latino immigrants, the health status of this group has important consequences for U.S. population health and for the health care delivery system. Research shows that among Hispanic/Latino immigrants in the U.S., Mexican women are at particularly high risk for developing depressive symptomology, suggesting that nativity and gender shape depression outcomes in critical ways [2][3][4][5][6]. It has long been presumed that culture also plays a role in shaping the lived experience of immigrants coming from different places and at different stages in their lives, though identifying the underlying mechanisms by which culture impacts health outcomes has been difficult to document empirically in social scientific research [7,8].…”
Section: Introductionmentioning
confidence: 99%